Organ specific optical imaging of mitochondrial redox state in a rodent model of hereditary hemorrhagic telangiectasia‐1. Issue 10 (6th June 2013) - Ghanian, Zahra; Maleki, Sepideh; Park, SunYoung; Sorenson, Christine M.; Sheibani, Nader; Ranji, Mahsa
Abstract Hereditary Hemorrhagic Telangiectasia‐1 (HHT‐1) is a vascular disease caused by mutations in the endoglin (Eng)/CD105 gene. The objective of this study was to quantify the oxidative state of a rodent model of HHT‐1 using an optical imaging technique. We used a cryofluorescence imaging instrument to quantitatively assess tissue metabolism in this model. Mitochondrial redox ratio (FAD/NADH), FAD RR, was used as a quantitative marker of the metabolic status and was examined in the kidneys, and eyes of wild‐type and Eng +/– mice. Kidneys and eyes from wild‐type P21, 6W, and 10M old mice showed, respectively, a 9% (±2), 24% (±0.4), 15% (±1), and 23% (±4), 33% (±0.6), and 30% (±2) change in the mean FAD RR compared to Eng +/– mice at the same age. Thus, endoglin haploinsufficiency is associated with less oxidative stress in various organs and mitigation of angiogenesis. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)